2019
DOI: 10.1002/bip.23321
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the mechanical and physicochemical properties of cross‐linked protein films

Abstract: Films derived from natural sources such as proteins provide an advantage over synthetic films due to their noncytotoxicity, biodegradability, and vast functionality. A new protein source gained from the cataractous eye protein isolate (CEPI) obtained after surgery has been investigated for this purpose. Glycerol has been employed as the plasticizer and glutaraldehyde (GD) as a cross‐linker. Fourier transform infrared spectroscopy was employed to characterize the films. Nanoindentation and thermogravimetric ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 72 publications
1
8
0
Order By: Relevance
“…The images of the PS film and cross-linked PSN4 film are shown in Figure (other images have been shown in Figure S2, Supporting Information). All the films were found to have a rough surface with a porous morphology, which are consistent with previously reported CEPI films from this laboratory. It was observed that the rough surface of the films had small pores (indicated with yellow arrows in Figure ). The roughness of the films reduces upon cross-linking following a reduction in the pore size with a concomitant increase in the number of pores.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The images of the PS film and cross-linked PSN4 film are shown in Figure (other images have been shown in Figure S2, Supporting Information). All the films were found to have a rough surface with a porous morphology, which are consistent with previously reported CEPI films from this laboratory. It was observed that the rough surface of the films had small pores (indicated with yellow arrows in Figure ). The roughness of the films reduces upon cross-linking following a reduction in the pore size with a concomitant increase in the number of pores.…”
Section: Resultssupporting
confidence: 88%
“…Earlier it was observed that the proteins extracted from the processing of lens emulsions discarded postsurgery, i.e. cataractous eye protein isolate (CEPI), are capable of film formation with tunable properties. However, the possibility of employing this protein for the construction of SPEs has not been explored. The human eye lens is abundant with lens Crystallin proteins that comprise ∼90% of the total lens proteins that retain lens transparency with their high refractive index .…”
Section: Introductionmentioning
confidence: 99%
“…Water-soluble γ-crystallin is found to be present in the supernatant post centrifugation . Following a previous procedure from our lab, we have obtained γ-crystallin from the CEPI. ,, In addition, theoretical trypsin digestion was performed on the sequence of human γ-crystallin. The result of the cleavage of γD crystallin (PDB ID: 1HK0) is shown in Table (γB and γC crystallin are shown in Tables S1 and S2 of the Supporting Information, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…31 Following a previous procedure from our lab, we have obtained γ-crystallin from the CEPI. 25,31,32 In S1 and S2 of the Supporting Information, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation